ALIGNING ENTREPRENEURIAL INTENTION TOWARDS SUSTAINABLE DEVELOPMENT AMONG MUSLIM YOUTH IN INDONESIA (JOURNAL OF INDONESIAN ISLAM, 2020)
The purpose of this paper is to examine the influence of entrepreneurial intention of the youth Muslim on the realization of maqasid al-shari‘ah in order to overcome poverty and unemployment problems to achieve the sustainable development agenda. This paper also attempts to fit in and enrich the literatures of entrepreneurial intention which integrates with maqasid al-shari‘ah as the objectives of Islamic teachings. An exploratory method design and a deductive approach employed in this study with respondent of 740 Muslim students from five provinces in Indonesia. The findings illustrate that religious and moral motivations have become an inseparable variable for developing entrepreneurial intentions among young people. The analysis output also indicates that subjective norms as the strongest driver to influence Muslim youth entrepreneurial intention. In addition, this study also has policy-level implication both for related government institutions and the universities.